A Comparative-Informational Approach to the Study of Religion: The Chinese and Jewish Cases. (12th October 2019) - Lior, Yair
Abstract: This article offers a "comparative-informational" approach to the study of religion. It demonstrates how historical transformations in religious traditions are frequently intertwined with shifts towards new strategies of managing information, or "informational orders." The article shows how two unrelated schools of thought—Neo-Confucianism and Kabbalah—were responsible for the construction and institutionalization of new information strategies in their respective traditions. The innovative discourses Neo-Confucians and Kabbalists established were characterized by "analytic" qualities that were co-opted from competing foreign traditions. As part of the Confucian and Jewish reactions to Buddhism and Greek philosophy, respectively, Neo-Confucian and medieval Jewish mystical discourses underwent considerable rationalization. Moreover, from an informational perspective, a major factor in the dramatic cultural transitions that Neo-Confucians and Kabbalists facilitated was the ability of these schools to restructure the canonical literature of their respective traditions. Such rare modificiations in a tradition's "informational core" are here interpreted as adaptive strategies that drive cultural systems towards greater complexity and long-term resilience.